2013
DOI: 10.1097/bsd.0b013e3182400897
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Subcutaneous Closed-suction Drainage and Conventional Closed-suction Drainage in Adolescents Idiopathic Scoliosis Patients Undergoing Posterior Instrumented Spinal Fusion

Abstract: The data suggest that subcutaneous closed-suction drainage offers a reasonable alternative to closed-wound suction drainage in adolescents idiopathic scoliosis patients undergoing posterior instrumented spinal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Diab et al 60 evaluated closed suction drainage in patients undergoing posterior fusion for idiopathic scoliosis and similarly found no difference in SSI rate or other complications in patients receiving drains versus no drains, with a higher transfusion rate in the drained group. In a randomized trial, Liang et al 61 evaluated the efficacy of subcutaneous closed-suction drains versus conventional drains following scoliosis surgery and found that subcutaneous closed-suction drainage offer a reasonable alternative to conventional deep drains. Although the use of drains is controversial, these studies did not find an increase in SSI rate with the use of surgical drains.…”
Section: Surgeon Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diab et al 60 evaluated closed suction drainage in patients undergoing posterior fusion for idiopathic scoliosis and similarly found no difference in SSI rate or other complications in patients receiving drains versus no drains, with a higher transfusion rate in the drained group. In a randomized trial, Liang et al 61 evaluated the efficacy of subcutaneous closed-suction drains versus conventional drains following scoliosis surgery and found that subcutaneous closed-suction drainage offer a reasonable alternative to conventional deep drains. Although the use of drains is controversial, these studies did not find an increase in SSI rate with the use of surgical drains.…”
Section: Surgeon Factorsmentioning
confidence: 99%
“…Diab et al 60 evaluated closed suction drainage in patients undergoing posterior fusion for idiopathic scoliosis and similarly found no difference in SSI rate or other complications in patients receiving drains versus no drains, with a higher transfusion rate in the drained group. In a randomized trial, Liang et al 61 evaluated the efficacy of subcutaneous closed-suction drains versus conventional drains…”
Section: Closed Suction Drainsmentioning
confidence: 99%
“…Liang et al performed a prospective, randomised controlled clinical study to evaluate the efficacy of subcutaneous closed-suction drainage in comparison with conventional closed-suction drainage [16]. A total of 105 patients undergoing posterior instrumented spinal fusion due to adolescent idiopathic scoliosis were randomised into one of the two groups.…”
Section: Subfascial Versus Subcutaneous Drainagementioning
confidence: 99%
“…All other measurements showed no differences between groups. Liang et al included 105 patients and compared subcutaneous versus conventional closed-wound suction drainage systems [16]. The core temperature was higher (p = 0.001) and the duration of fever was longer (p = 0.008) in the subcutaneous drainage group.…”
Section: Postoperative Fevermentioning
confidence: 99%
“…Typically, the discharge hemoglobin after surgery for spinal deformity has been reported to be approximately 10 g/dL. 85,86 Edwards et al 87 conducted a retrospective chart review of 475 patients at a single institution on multiple specialty services. They found that discharge hemoglobin was a significant indicator of overutilization of blood transfusion and that a large portion of patients who had discharge hemoglobin of 10.0 g/dL or more could have avoided at least 1 unit of blood transfusion.…”
Section: Indications To Transfusementioning
confidence: 99%